The culture of the South African sugarmill : the impress of the sugarocracy - Lincoln, Mervyn David (Department of Sociology, 2016)
In this thesis an analysis is made of the relationship between the families which until recently controlled most of South Africa's sugarmills, and their sugarmill employees. The relationship is approached by way of a study of the culture of the sugarmill; by way, that is, of looking at the ideological and material connotations of the sugarmilling labour process as they manifested themselves in the sugar villages of South Africa. It is the principal concern of the study to demonstrate how the dynastic sugarmilling families, who are presented as a sugarocracy, impinged upon the culture of the sugarmill. By perceiving the culture of the sugarmill as evolving out of the sugarmilling labour process, a materialist interpretation of historical evidence is indicated as a method for analysing sugarocratic domination. This method is applied to empirical evidence derived primarily through literary research. A further methodological consideration is displayed in the emphasis given to causal relationships between sugarocratic influences upon the labour process and workers' responses to that process. Because of the centrality accorded to the labour process points of reference are readily found in studies of sugarmilling in other milieux. Thus each chapter of the thesis is introduced with relevant material on sugarmilling in regions where it has generally been subjected to more social analysis than has been the South African case. Arranged in three parts, the analysis begins with an account of the ascent of the sugarocracy since the turn of the twentieth century, and of the establishment and development of sugarocratic ideology and politics. In the second part, attention is focused on the sugarmill, with chapters devoted to sugar technology and the technical division of labour, the racial division of labour, and work-place control, respectively. The final part is given to an examination of life in the sugar village, and to the question of how, by means of accommodation and resistance, workers coped with the conditions under which they worked and lived.